2001
DOI: 10.1046/j.1365-2141.2001.02826.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Vγ/Jβtrans‐rearrangements in paediatric patients undergoing chemotherapy

Abstract: Summary. The frequency of the hybrid Vg/Jb transrearrangement in peripheral blood lymphocytes (PBLs) was analysed in a transversal study of paediatric patients (n 210) with acute lymphoblastic leukaemia (ALL) and solid tumours (ST). Different amounts of DNA were used as the template for a nested polymerase chain reaction to evaluate the frequency of hybrid Vg/Jb genes, using silverstained gels. The frequency of the rearrangement was evaluated in groups before, during and after therapy. A greatly increased freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
(42 reference statements)
0
3
0
1
Order By: Relevance
“…It has been suggested that the absolute number of "innocent" trans-rearrangements with both breakpoints in TCR gene loci correlates with the risk of lymphoma, regardless of whether that risk is based on an inherited predisposition or acquired exposure. An assay of trans-rearrangements may serve as a biomarker of lymphoma risk (Lipkowitz et al 1992;Lista et al 1997;Kirsch 1997;Lopes et al 2001;Allam and Kabelitz 2006). An increased number of innocent trans-rearrangements involving TRA/TRD in pigs may thus indicate a higher risk of T-cell lymphoma than in humans.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been suggested that the absolute number of "innocent" trans-rearrangements with both breakpoints in TCR gene loci correlates with the risk of lymphoma, regardless of whether that risk is based on an inherited predisposition or acquired exposure. An assay of trans-rearrangements may serve as a biomarker of lymphoma risk (Lipkowitz et al 1992;Lista et al 1997;Kirsch 1997;Lopes et al 2001;Allam and Kabelitz 2006). An increased number of innocent trans-rearrangements involving TRA/TRD in pigs may thus indicate a higher risk of T-cell lymphoma than in humans.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, in humans and mice, these trans-rearrangements have been studied by PCR (Tycko et al 1989;Lipkowitz et al 1990;Kobayashi et al 1991;Lista et al 1997). Increased levels of trans-rearrangements were observed in farmers exposed to pesticides (Lipkowitz et al 1992) and in oncological patients undergoing chemotherapy (Abdallah et al 1995;Lopes et al 2001). The effect of chemotherapy was transient, and the study in paediatric patients showed that higher levels were exhibited only in patients homozygous for the wild type of CYP3A4 (Lopes et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Intriguingly, the frequency of TCR trans-rearrangements can rapidly increase in some situations. Several fold increases in the frequency of trans-rearrangements were seen in patients undergoing chemotherapy for the treatment of lymphomas, leukemias, or solid tumors (39,40). This increase was transient and returned to the basal level after cessation of chemotherapy.…”
Section: Increase In V(d)j Trans-rearrangements In Pathological and Pmentioning
confidence: 92%
“…33 Watanabe e cols estudaram a influência do "Brazilian ginseng" e o aparecimento de leucemias em estudo experimentais. 34 Também a instabilidade genética em pacientes pediátricos expostos a quimioterápicos foi recentemente publicado 35 e já referida anteriormente. folato 40 e que, repostos adequadamente, trazem recuperação da leucometria em 24 horas (geralmente), freqüentemente sob a forma de leucocitoses, às custas de neutrofilia e desvio à esquerda, traduzindo a resposta (agora adequada) ao estresse inflamatório (informação pessoal).…”
Section: Diagnóstico Morfológicounclassified